The mechanism of high-quality logistics in rural industrial upgrading—A dual moderation perspective of technological innovation and digital finance - Borui Yan; Bo Yao; Qianyu Guo; Xiaonan Zhang (PLoS ONE, 2026)
High-quality logistics development plays a crucial role in upgrading the rural industrial structure. It aims to explore the impact mechanism and underlying logic of high-quality logistics development on the upgrading of rural industry. By constructing an empirical model and utilizing statistical data from 30 provinces in China from 2011 to 2022, it analyzes the role of high-quality logistics development in promoting rural industrial upgrading. Furthermore, it examines the mediating, moderating, and threshold effects of factors such as regional industrial structure, fiscal support for technological innovation, digital finance, agricultural labor productivity, and the urban-rural income gap. The results indicate that high-quality logistics development significantly promotes rural industrial upgrading, and this effect remains robust after incorporating control variables. Moreover, regional industrial structure acts as a mediating effect to strengthen this positive impact; enhanced fiscal support for technological innovation and digital finance further amplify the effect; and agricultural labor productivity and the urban-rural income gap present significant threshold effects, leading to heterogeneous impacts of high-quality logistics development across different levels of these factors.